2000
DOI: 10.1021/jp993163m
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cl Atom Reactions with C2H5Cl and C2H4Cl Radical and the Disproportionation of 2C2H4Cl at 298 K and at Millitorr Pressures

Abstract: The bimolecular reaction Cl + C2H5Cl → HCl + C2H4Cl (1) is studied in the very-low-pressure reactor (VLPR) system at room temperature. Detailed mass spectrometric analysis of simultaneous reactant consumption and product formation rates indicates that the overall mechanism also includes two disproportionation reactions:  Cl + C2H4Cl → HCl + C2H3Cl (2) and 2C2H4Cl → C2H5Cl + C2H3Cl (3). Rate constants obtained for these reactions are:  k 1 = (8.07 ± 0.36) × 10-12, k 2 = (1.18 ± 0.06) × 10-11, and k 3 = (1.83 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 28 publications
4
18
1
Order By: Relevance
“…Both of these complications can be minimized by judicious choice of initial concentrations. A few reports exist for very low pressure conditions (VLPR) with mass spectroscopic detection, , but the reliability of the technique has been questioned …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of these complications can be minimized by judicious choice of initial concentrations. A few reports exist for very low pressure conditions (VLPR) with mass spectroscopic detection, , but the reliability of the technique has been questioned …”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that k for polyfluoroalkanes is inversely proportional to their computed hardness, that is, (IE – EA)/2; in other words, increasing softness promotes charge transfer and facilitates reaction . An attempt to apply Pauling electronegativities to correlate k for polychloro ethers was only modestly successful; this independent variable was also suggested for alkyl halides . Unfortunately, these independent variables are not widely available for the cases in Table .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative decomposition of halogenated hydrocarbons have been investigated on a number of occasions. , Recent studies suggest that the thermal decomposition of chlorinated straight-chain hydrocarbons proceeds via a unimolecular C–Cl bond scission at the allylic carbon, due to this C–Cl bond being weaker compared to other C–H bonds. , The primary chemical products (∼90%) of 1,3-D thermolysis are CO, CO 2 , H 2 O, and HCl . HCl formation can occur via H abstraction by Cl from the parent compound and its derived radicals or via an intra-annular HCl elimination. ,,, However, combustion of non-chlorinated analogous species shows that O 2 abstraction of an allylic H, forming the HO 2 radical, is also an important initiation step. This HO 2 radical is converted to the relatively more stable OH radical by reactions with 1,3-D and allylic radicals, additionally forming aldehydes/ketones and aldehydic/ketonic radicals. The latter can undergo unimolecular or bimolecular C–C bond scissions to form CO or react with O 2 to form an alkylperoxy radical, which can readily react with alkenes to form alkoxides and CO 2 . H 2 O is formed mainly by abstraction or combination reactions of H with OH. ,, Previously, molecular dynamics (MD) has proved to be an invaluable tool in revealing reaction initation pathways in the combustion of methane, , n -dodecane, phenol, , and benzene . However, the ...…”
Section: Introductionmentioning
confidence: 99%
“…Kaiser et al , have studied the CH 3 CHCl + Cl 2 reaction with respect to the CH 3 CHCl + O 2 reaction using relative rate method and initiating the reactions using 351 nm photolysis of Cl 2 in a reaction cell ( T = 298 K, 700 Torr of N 2 ) and employing absorption spectroscopy for product analysis. Dobis and Benson measured the kinetics of CH 3 CHCl + Cl 2 reaction under very low pressure conditions (VLPR-method) at room temperature.…”
Section: Introductionmentioning
confidence: 99%